Collision risk modelling for tidal energy devices: A flexible simulation-based approach. (15th January 2021) - Horne, Nicholas; Culloch, Ross M.; Schmitt, Pál; Lieber, Lilian; Wilson, Ben; Dale, Andrew C.; Houghton, Jonathan D.R.; Kregting, Louise T.
Abstract: The marine renewable energy industry is expanding as countries strive to reach climate targets as set out in the Paris Agreement. For tidal energy devices, the potential risk for animals to collide with a device, particularly its moving parts such as rotor blades, is often a major barrier in the consenting process. Theoretical work surrounding collision risk has commonly made use of a formulaic modelling approach. However, whilst providing a platform to assess conventional horizontal axis tidal turbines, the frameworks applied lack the flexibility to incorporate novel device designs or more complex animal movement parameters (e.g. dive trajectories). To demonstrate the novel simulation-based approach to estimating collision probabilities a hypothetical case study was used to demonstrated how the approach can assess the influence that variations in ecological and behavioural data had on collision probabilities. To do this, a tidal kite moving in a 3D figure-of-eight trajectory and a seal-shaped object were modelled and variations to angle of approach, speed and size of the animal were made. To further improve the collision risk estimates, results of the simulations were post-processed by integrating a hypothetical dive profile. The simulations showed how variation in the input parameters and additional post-processing influence collision probabilities. Our results demonstrate the potential for using this simulation-based approach for assessing collision risk, highlighting the flexibility it offers by way of incorporating empirical data or expert elicitation to better inform the modelling process. This framework, where device type, configuration and animal-related parameters can be varied with relative simplicity, on a case-by-case basis, provides a more tailored tool for assessing a diverse range of interactions between marine renewable energy developments and receptors. In providing a robust and transparent quantitative approach to addressing collision risk this flexible approach can better inform the decision-making process and aid progress with respect to developing a renewable energy industry in a sustainable manner. Therefore, the approach outlined has clear applications that are relevant to many stakeholders and can contribute to our ability to ensure we achieve sustainable growth in the marine renewable energy industry as part of a global strategy to combat climate change. Graphical abstract: Image 1 Highlights: A flexible simulation-based approach to collision risk modelling for tidal energy devices is presented. Using many simulations, collision probabilities were calculated and compared for a kite and tether based tidal energy device and an approaching animal. The simulations demonstrated the ability to alter input parameters such as animal speed, size, and angle approach, which allows for the use of considered and realistic parameters. Further refinements of collision probabilities were made by post-processing results to integrate data from animal dive profiles. Our approach offers advantages over previous models and will be of use to environmental researchers and regulators around the world.